Dilemma regarding the reorganization of the branch office of a society established abroad Corporate transformation or a conversion into a society? - Hundskopf Exebio, Oswaldo (2024)
For the purposes of this article, it should be considered that branches of companies are extensions that operate outside the main headquarters and are subject to local laws. Their creation and operation are regulated by the General Law of Companies (LGS), which establishes requirements such as registration and the appointment of a representative. These branches may carry out the activities authorized by the parent company, but they may not enter into contracts that exceed their scope. One of the most relevant aspects to be discussed is the possibility of transforming a foreign branch into a national company. This transformation, considered an exception, has the capacity to allow the branch to acquire its own legal personality. Through the explanation of the dilemma, branches of Peruvian companies are presented as a tool for expanding operations and offering services. In this way, the transformation of a branch into a Peruvian company, although exceptional, provides greater legal flexibility.